THE IMPLEMENTATION OF SAME-RELIGION MARRIAGE LAWS TO STRENGTHEN INTERFAITH TOLERANCE - Muhammad Shodiqin, Muhammad Zakki, Mohamad Farid, Wakid Evendi (Integrative Perspectives of Social and Science Journal, 2025)
Tolerance between religious communities in the diversity of Indonesian society is a part that continues to be upheld and guaranteed in the 1945 Constitution to ensure harmony in community life so that consistency in practicing religion and belief is needed in fostering a spirit of tolerance. The practice of applying same-religion marriage that has been stipulated in Law 1/1974 is considered an attitude of religious intolerance in multicultural community life, which ultimately reaps prolonged debate and polemic until now, even though the application of same-religion marriage is a forum for the Indonesian state in maintaining harmony and peace in the lives of religious believers who do not interfere with each other's religious rights and obligations. This research shows whether same-religion marriage in Indonesian marriage law increases tolerance between people of different religions and strengthens consistency in religion. To help find answers to this research, The author's approach for this research is a type of qualitative research that uses data sources such as papers, scientific journals, legislation, decisions, and other sources. The data is carefully studied and analyzed to get the right answer to the problem under study. From this research, it is concluded that the implementation of same-religion marriage in Indonesian marriage law can increase tolerance among religious people in community diversity, because of the growing consistency of adherents of each religion in developing their respective religious teachings which are influenced by the existence of understanding and self-awareness among religious people.